2021
DOI: 10.1016/j.ymthe.2020.09.039
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2/3 Trial of Pabinafusp Alfa, IDS Fused with Anti-Human Transferrin Receptor Antibody, Targeting Neurodegeneration in MPS-II

Abstract: Pabinafusp alfa (JR-141) is a novel enzyme drug that crosses the blood-brain barrier by transcytosis via transferrin receptors. In order to establish its efficacy and safety, a multicenter, singlearm, open-label phase 2/3 clinical trial was conducted in 28 Japanese patients with mucopolysaccharidosis II (MPS-II, Hunter syndrome) by intravenous administrations of 2.0 mg/kg of pabinafusp alfa for 52 weeks. The primary efficacy endpoint was changes in heparan sulfate (HS) concentrations in the cerebrospinal fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 26 publications
3
88
0
Order By: Relevance
“…A phase I/II clinical trial (NCT03128593) in 14 patients with MPS II resulted in significant reduction of HS levels in the CSF at a dose of 2 mg/kg/week [254]. The subsequent phase II/III clinical trial (NCT03568175) not only confirmed HS level reduction, but also demonstrated improved neurocognition in 21/28 patients [255]. A Brazilian phase I/II dose-escalation clinical trial (NCT03359213) confirmed the 2 mg/kg/week dose as most effective with minimal side effects [256].…”
Section: Shuttling Of Ids Across the Bbbmentioning
confidence: 99%
“…A phase I/II clinical trial (NCT03128593) in 14 patients with MPS II resulted in significant reduction of HS levels in the CSF at a dose of 2 mg/kg/week [254]. The subsequent phase II/III clinical trial (NCT03568175) not only confirmed HS level reduction, but also demonstrated improved neurocognition in 21/28 patients [255]. A Brazilian phase I/II dose-escalation clinical trial (NCT03359213) confirmed the 2 mg/kg/week dose as most effective with minimal side effects [256].…”
Section: Shuttling Of Ids Across the Bbbmentioning
confidence: 99%
“…14 As a result, pabinafusp alfa reduces elevated GAG levels in the CNS, as well as in peripheral tissues in a mouse model of MPS II. [14][15][16][17] The major GAG species accumulated in the body of patients with MPS II are HS and DS. 18 Although the precise roles of HS and DS in CNS pathogenesis of the disease are not fully understood, cells in the CNS seem to be more susceptible to HS than to DS.…”
Section: Introductionmentioning
confidence: 99%
“…Age equivalent scores in the phase II and phase II/III studies in patients with the severe subtype of MPS-II, overlaid onto the corresponding developmental trajectories from the natural history data. JR-141-BR21/BR22 stands for the phase II study in Brazil and its extension study; JR-141-301/302 indicates the phase II/III study in Japan and its extension study (updated from [14] and [15]).…”
Section: Neurocognitive Efficacymentioning
confidence: 99%
“…These promising preclinical data prompted the first human phase I/II study in Japan involving patients with MPS-II, which also produced encouraging results [13]. The subsequent phase II study in Brazil [14] and a phase II/III study in Japan [15] further substantiated the somatic/peripheral and central efficacy of pabinafusp alfa, leading to its regulatory approval for general use in Japan in March 2021 as the first BBB-crossing ERT. This article reports an integrated analysis of the hitherto accumulated preclinical and clinical data, including the latest long-term efficacy and safety data from the ongoing extension studies in the two countries, as well as some of the methodological and scientific challenges that had to be overcome in preclinical and clinical evaluations of the drug's efficacy against complex progressive neurodegeneration.…”
Section: Introductionmentioning
confidence: 97%